Thee level of eicosapentaenoic (EPA),but not docosahexaenoic acid (DHA) is related to formulation and concentration of EPA and DHA in feed - Seternes, Tore; Johansson, Gunhild S.; Evje, Iselin; Olsen, Ragnar Ludvig (Aquaculture, 2020)
The present study investigated how the concentration of PUFA in blood and muscle of Atlantic salmon ( Salmo salar L.) changed when fed 4 diets containing very different amounts of LC-PUFA in fresh water for 84 days. The n-3 LC-PUFA constituted 4.4, 24.2, 18.4, and 51.5% of the total fatty acids in the diets made with rapeseed oil, anchoveta oil, a combination of rapeseed oil (60%) and anchoveta oil (40%), and EPA/DHA concentrate, respectively. No significant differences in the growth were observed in the groups during the feeding experiment. The changes in n-3 LC-PUFA in blood and muscle were however quite different in the 4 feeding groups. In the blood, DHA was mobilised to or retained at high level (30–36%) even with a very low amount of DHA in the feed. The concentration of EPA in the blood reflected to a large degree the concentration in the feed, with a rapid increase of EPA in the blood during the first 21 days of feeding. The level of EPA in the blood remained at this level for the rest of the study. However, when only small amounts (1.8%) were present in the feed the fatty acid appeared to be selectively mobilised to or retained in the blood. In the muscle, the percentage of EPA, DHA and other fatty acids mirrored the amounts in the feed suggesting increased TAG (triacylglycerides) during the feeding period.